Analysis of Information Technology Strategy in Multifinance Companies Based on Digital Present Information Website - Harias Kalbuadi (Jurnal Indonesia Sosial Teknologi, 2024)
Technology is needed both in the process of collecting data, information and activities to reduce the use of paper or paperless. According to OJK, a Financing Institution is a business entity that carries out financing activities in the form of providing funds or capital goods. Some of the benefits of IT strategy Making a roadmap for IT development and development both related to infrastructure, application systems, services and information security. With the data and information that can be collected, it can be managed and used in decision making through an analysis that can be used in looking at the policies and strategic decisions of the organization. With the IT strategy, companies can have strategies in securing data and system management in the organization, in particular, with the IT strategy, it can be used to segment the market and determine business focus to increase added value that can be provided to consumers or debtors. From making a checklist using the websites of 26 finance companies, it can be seen that the company's strategy in digitalization and information technology such as having applications, ISO 270001 standards, using marketing and payment channels as well as the use of financing glorification forms and financing applications shows that multifinance companies have begun to move to digitalization. If a multifinance company has an aggressive vision for asset development and digital present, digital channels are enhanced to increase the number of potential new customers entering through digital channels and of course by improving and maintaining data quality by using third party data and increasing payment channel cooperation to ensure more choice of debtor payments. With a moderate vision, the use of third party data to improve credit quality to improve or improve the quality of the asset portfolio of multifinance companies.